Pengembangan Media Pembelajaran Software Multimedia (Audacity Dan Wondershare Filmora) Berbasis Learning Management System Pada Mata Kuliah Audio Video Editing - Riko Hutomo; Dr. Nyoman Santiyadnya, S.Si., M.T.; Dr. I Putu Suka Arsa, S.T., M.T. (Universitas Pendidikan Ganesha, 2024)
This research aims to create multimedia learning materials (using Audacity and Wondershare Filmora) through a Learning Management System (LMS), assess their feasibility, and determine the students' responses to these multimedia learning materials in the Audio-Video Editing course. The research employs the Research and Development (R&D) methodology. Data collection is carried out using questionnaires, which are evaluated by content experts, media experts, and active students in the Electrical Engineering Education program at Undiksha. The results of the research are as follows: The validation results from content experts achieved a percentage of 88.46%, qualifying as highly suitable. The validation results from media experts reached a percentage of 92%, also qualifying as highly suitable. Small group trial results with 5 respondents all qualified as very good. The large group trial results with 15 respondents all fell into the category of very good. Based on the research findings, the development of multimedia software (Audacity and Wondershare Filmora) using a Learning Management System in the Audio-Video Editing course is considered suitable for use in the audio-video editing learning process.